Surface Morphology of a Microplastic as an Indicator of Its Microscale Degradation - Majewski, Kamil Artur; Myszograj, Sylwia; Płuciennik-Koropczuk, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Most of the plastic produced, being one-use plastic packaging, is finally disposed of into the environment. Several agents such as solar radiation, mechanical forces, and microbial action may enable the degradation of these plastics. The purpose of this article is to present a method for studying the properties of a surface of a microplastic particle affected by erosion at the microscale level, which occurred with the help of destructive forces associated with the impact of the sea.
Keywords: plastic packaging; one-use packaging; microplastics; degradation; polypropylene; analytical methods; opakowanie plastikowe; opakowanie jednorazowego użytku; mikroplastik; degradacja; polipropylen; metoda analityczna